Considerations for the need of recommendations for the research and publication of DNA methylation results. (November 2018) - Naue, Jana; Lee, Hwan Young
Highlights: DNA methylation is an important tool for forensic applications. DNA methylation analysis differs from the STR/SNP analysis and needs special attention. No recommendations are available yet to facilitate current research and publication. We provide a first collection of possible recommendations. We want to open the discussion for further proper guidelines usable in casework.